2017
DOI: 10.1001/jamaneurol.2017.1658
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Midlife Vascular Risk Factors and 25-Year Incident Dementia in the Atherosclerosis Risk in Communities (ARIC) Cohort

Abstract: IMPORTANCE Vascular risk factors have been associated with cognitive decline. Midlife exposure to these factors may be most important in conferring late-life risk of cognitive impairment.OBJECTIVES To examine Atherosclerosis Risk in Communities (ARIC) participants in midlife and to explore associations between midlife vascular risk factors and 25-year dementia incidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
403
1
13

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 482 publications
(432 citation statements)
references
References 34 publications
15
403
1
13
Order By: Relevance
“…Similar to early interventions in midlife to prevent CVD, addressing these modifiable factors to prevent early changes in neurologic health may reduce or delay brain aging. [3][4][5][6]9,10 The innovative component of our study was the use of a composite measure of sensorineural and neurocognitive function as a marker of brain aging. Longitudinal studies found that sensorineural impairments in hearing, vision, and olfaction predict cognitive decline or impairment, [11][12][13][14]17 suggesting that sensorineural functions may be sensitive to early effects of pathophysiologic aging processes or aging changes may occur early in brain regions associated with sensorineural function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to early interventions in midlife to prevent CVD, addressing these modifiable factors to prevent early changes in neurologic health may reduce or delay brain aging. [3][4][5][6]9,10 The innovative component of our study was the use of a composite measure of sensorineural and neurocognitive function as a marker of brain aging. Longitudinal studies found that sensorineural impairments in hearing, vision, and olfaction predict cognitive decline or impairment, [11][12][13][14]17 suggesting that sensorineural functions may be sensitive to early effects of pathophysiologic aging processes or aging changes may occur early in brain regions associated with sensorineural function.…”
Section: Discussionmentioning
confidence: 99%
“…These factors are consistent with those reported in previous studies of sensorineural or neurocognitive function. [3][4][5]7,[9][10][11]26,[36][37][38][39][40][41] Notably, IL-6 and sICAM-1 were associated with prevalent and incident brain aging, respectively. Higher levels of systemic inflammation may both directly, and through its deleterious effects on vascular health, promote or accelerate pathophysiologic aging changes.…”
Section: Discussionmentioning
confidence: 99%
“…; Gottesman et al. ). The Cyp1a1‐Ren2 rat model has not previously been used to study the effects of hypertension on cognition.…”
Section: Discussionmentioning
confidence: 98%
“…In fact, even in prehypertensive (systolic BP >120 and <140 mm Hg or diastolic BP >80 and <90 mm Hg) middle-aged adults, an elevated systolic BP level was shown to be negatively associated with cognitive performance, including memory and executive function [8]. In a cohort study, prehypertension in midlife was also shown to be associated with increased risk of developing dementia [25]. Another study found significantly worse performance on verbal episodic memory for untreated hypertensive women; even at the prehypertensive level, the predictive performance on memory domain is less satisfactory later in life [7].…”
Section: Hypertension and Cognitive Dysfunction In Midlifementioning
confidence: 99%